Implementasi Pendidikan Karakter Sopan Santun Siswa Di MTsS Irsyadul Wathan Nagari Baruah Gunuang Kecamatan Bukik Barisan Kabupaten Lima Puluh Kota - Syarifah Adillah; Jasmienti Jasmienti; Alimir Alimir; Khairuddin Khairuddin (LP3M KH Yazid Karimullah Institute, 2023)
The author's background in conducting this research is the problem of polite character education. The aims of this study were: 1) To find out the Implementation of Polite Character Education for Grade VIII Students to Teachers at MTsS Irsyadul Wathan Nagari Baruah Gunuang 2) To find out the Implementation of Polite Character Education for Grade VIII Students to Friends at MTsS Irsyadul Wathan Nagari Baruah Gunuang. This research is an empirical research using a source of knowledge obtained from observation and also findings in the field, using a qualitative approach. The author's data collection is done by observation, interviews and documentation. The key informants in this study were students and supporting informants, namely principals and teachers at MTsS Irsyadul Wathan. As for data analysis using data reduction, data presentation and temporary conclusions in this study using data triagulation. Based on the results of the study it can be found that, the implementation of character education of class VIII students' courtesy towards the teacher 1. Students' polite attitude in respecting the teacher, 2. Students sit politely and speak respectfully, 3. Students listen to the teacher when talking and do not interrupt the teacher's conversation. 3. Shiva does not offend the teacher. While the implementation of politeness character education for class VIII students to friends is 1. Students say hello every time they meet friends, 2. Avoid hostility with friends, 3. Insult and belittle friends, 4. Forgive each other if they forget or accidentally make mistakes, 5 Advise friends if there are friends who are stingy and arrogant.